Peran Mediasi Struktur Modal dalam Hubungan Profitabilitas dan Firm Size terhadap Nilai Perusahaan - Yulianti, Dwi; Puspitasari, Intan; Utomo, Agus Saur (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The purpose of this study was to determine the effect of profitability and company size on firm value with capital structure as an intervening variable in property and real estate companies listed on the Indonesia Stock Exchange (BEI). This research is quantitative research that uses secondary data with a sample size of 23 from 52 companies taken based on purposive sampling, namely a sample selection method by establishing certain criteria. The period used is five years, starting from 2018 to 2022. The method used in this research is path analysis and processed using WarpPLS version 8.0 software. The result of this study found that (1) profitability has a significant positive effect on firm value with a significant value of 0,01 which is smaller than 0,05 (0,01 < 0,05) (2) company size has a significant positive effect on firm value with a significant value of 0,01 which is smaller than 0,05 (0,01 < 0,05) (3) profitability has a significant negative effect on capital structure with a significant value of 0,01 which is smaller than 0,05 (0,01 < 0,05) (4) company size has a significant positive on capital structure with a significant value of 0,01 which is smaller than 0,05 (0,01 < 0,05) (5) capital structure has a significant negative on firm value with a significant value of 0,01 which is smaller than 0,05 (0,01 < 0,05) (6) capital structure is able to mediate the effect of profitability on firm size on firm value with a coefficient of 0.027 which is smaller than 0.05 (0.027 < 0.05) (7) capital structure is able to mediate the effect of company size on firm size on firm value with a coefficient of 0.027 which is smaller than 0.05 (0.041 < 0.05).